Hematological and biochemical variables in hospitalized patients with clinical suspicion of dengue - Rolando Rodríguez Puga; Yoánderson Pérez Díaz; Yanet Pérez Guerrero; Serapio Romero Gavilán (Medisur)
Foundation: given the growing importance of dengue on a global and regional scale, timely determination of hematological and biochemical variations is required. In this sense, the pillars of treatment must be addressed to prevent complications that may be life-threatening. Objective: to describe the hematological and biochemical variables in hospitalized patients with clinical suspicion of dengue. Methods: a descriptive, cross-sectional study was carried out at the Amalia Simoni Provincial Clinical Surgical Teaching Hospital in Camagüey, from January to December 2022. A sample of 157 patients was used and the following variables were analyzed: age group, sex, hematological variables, values, day(s) of onset of symptoms, differential formula, biochemical and hematological variables, and differential formula with their paired differences. Results: The age group 40-49 years (28.7%) and male sex (50.3%) predominated. Leucopenia was found in 42.7% of patients and thrombocytopenia in 19.1%. Elevated hematocrit values were observed, especially in women (12.1%). Neutrophilia (50.0%) and lymphocytosis were noted in the differential formula between the fourth and sixth day of onset of symptoms. Predominant values of gamma glutamyl transferase were found in 45.2% and creatinine in 21.0%. Conclusions: The analysis allowed verifying significant statistical differences between the values of the leukocyte, neutrophil and lymphocyte counts on admission and on the third day. The enzymes aspartate aminotransferase and gamma glutamyl transferase were elevated in a representative percentage of cases.